Enhancing science performance of middle‐school students with and without developmental and behavioral‐based disabilities using the Content Acquisition Podcast Professional Development approach. Issue 3 (27th August 2022) - VanUitert, Victoria J.; Kennedy, Michael J.; Peeples, Katherine N.; Romig, John Elwood; Mathews, Hannah M.; Rodgers, Wendy J.
Abstract: Understanding science allows students with and without developmental and behavioral‐based (DB) disabilities to better appreciate the world around them as well as prepare them for the growing science‐related job market. However, students in the United States consistently underperform on science achievement tests compared to students from other nations. This underperformance could be attributed, in part to science having many specialized vocabulary terms that are not often taught explicitly, leaving students with incomplete or inaccurate understandings of word meanings. Improving science vocabulary instructional practices may support students with and without DB disabilities in enhancing their science achievement. To address this need, researchers implemented multicomponent multimedia professional development (PD) to support middle‐school science teachers in delivering high‐quality vocabulary instruction in inclusive settings. In this paper, data collected from a study evaluating the efficacy of the PD were analyzed to determine the influence on student outcomes using ANOVA and multilevel modeling methodologies. Though initial results indicate a promising impact on teacher instructional practices, little is known whether teacher participation in the PD affected student science vocabulary and content knowledge growth. Using multilevel modeling, student science knowledge growth was evaluated following their teachers' exposure to the PD. The findings from this study indicate having indirect exposure to PD had a positive effect on science content knowledge for students with and without DB disabilities ( N  = 980). In addition, the authors found students with DB disabilities whose teachers had access to PD showed a larger gain in science knowledge than general education students whose teachers did not have access to the PD.